2012
DOI: 10.1016/j.jhydrol.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated properties for non-Darcian water flow in clay

Abstract: Clay rock formations, and compacted clay (e.g., bentonite) used as backfill within disposal drifts, have been considered as natural and engineered barriers, respectively, for isolating high-level nuclear wastes in mined geologic repositories. Accurately modeling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 17 publications
1
21
0
1
Order By: Relevance
“…Cui et al (2008) reported non-Darcian behavior for a range of observed hydraulic gradients under unsaturated conditions. Liu et al (2012) developed a constitutive model for unsaturated flow when water can be considered as a power-law (non-Newtonian) fluid; the model is consistent with the data set of Cui et al (2008). Note that Liu et al (2012) probably were the first to report relative-permeability formulations for power-law fluids.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Cui et al (2008) reported non-Darcian behavior for a range of observed hydraulic gradients under unsaturated conditions. Liu et al (2012) developed a constitutive model for unsaturated flow when water can be considered as a power-law (non-Newtonian) fluid; the model is consistent with the data set of Cui et al (2008). Note that Liu et al (2012) probably were the first to report relative-permeability formulations for power-law fluids.…”
Section: Introductionmentioning
confidence: 74%
“…Liu et al (2012) developed a constitutive model for unsaturated flow when water can be considered as a power-law (non-Newtonian) fluid; the model is consistent with the data set of Cui et al (2008). Note that Liu et al (2012) probably were the first to report relative-permeability formulations for power-law fluids. Power-law fluids are common in the processes of enhanced oil recovery (EOR), such as chemical flooding.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, many evidences from the laboratory and field experiments show that this linear law may be invalid in some situations, especially when the groundwater flow velocity is sufficiently high or sufficiently low, where non-Darcian flow prevails (Basak, 1977;Bordier and Zimmer, 2000;Engelund, 1953;Forchheimer, 1901;Izbash, 1931;Liu et al, 2012;Soni et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al (2008) reported non-Darcian behavior for a range of observed hydraulic gradients under unsaturated conditions. Liu et al (2012) developed a constitutive model for unsaturated flow when water can be considered as a power-law (non-Newtonian) fluid. The model is consistent with the data set of Cui et al (2008).…”
Section: Introductionmentioning
confidence: 99%